REKAYASA TUNGKU BRIKET BATUBARA PADA PENGOVENAN DAUN TEMBAKAU VIRGINIA - SAMSURl TIRTOSASTRO; SOEBANDI SOEBANDI; DARMONO DARMONO (Pusat Penelitian dan Pengembangan Perkebunan, 2000)
Coal briquette furnace engineering for Virginia tobacco curingA coal briquette furnace for curing Virginia tobacco has been designed and constructed in Research Institute for Tobacco and Fiber Cops, Malang, East Java Indonesia. The furnace design was tested in East Lombok, Nusa Tenggara Barat, fom August to September, 1997. The goal of this research is to provide an alternative fuel for curing Virginia tobacco and its burning system for the product of Virginia tobacco. The coal briquette funace model is similar with wood funace with a brick wall. 125 cm long and 72% of that part positioned at the floor of the barn. The height of the curve furnace was 120 cm and the width was 105 cm. Terminal of the furnace hole was connected with the irst heat exchanger pipe made from iron plate (d = 58 cm) and than with the second heat-exchanger pipe (d = 30cm) encircle in the funace loor. Waste of the smoke coal burning was discharged through two chimneys of 5 m in height.The honey-comb coal biquette has 12.5 cm x 12.5 cm x 8 cm dimensions and 5 500-6 000 kcal or 23 027-25 121 kJ/kg calorific value. Result of the experiment showed that using of the coal briquette-fuel heat (35-70°C) in a suitable for curing tobacco leaves. The cured-leaves quality was as good as the standard. Coal briquette consumption was 5.54 pieces or 6.36/kg of cured-leaves. Based on the coal briquette price of Rp. 100 per piece, the tested pumace model gave the BC-ratio = 1.03, NPV Rp 994 218 and IRR 29.02%. The break-event point was achieved at the briquette price of Rp. 119.23/piece.